Silk in biomedical engineering: A review - Zubir, Nazira; Pushpanathan, K (International Journal of Engineering Inventions (IJEI), 2016)
The astounding biomaterial features of silk for example its high mechanical strength, biocompatibility and degradability have led to plethoric study on the silk properties. Tissue engineering and regenerative medicine are the fields that have been widely explored using silk scaffolds due to their mechanical stability. The mechanical stability of the scaffold is vital for the cells to adhere, expand, divide, proliferate and differentiate. Various types of connective tissues for examples tendon, ligament, bone and cartilage have been used. Apart from that, the scaffold should also display remarkable biocompatibility feature, should be porous with high surface area, should match the target tissue and reproducible. Another important aspect of the scaffold that needs significant consideration is the usage of nanoscale structure for the cells to be able to recognize and elicit response. Hence, nanofibres is the most suitable format of the artificial matrices to be considered in the tissue engineering technique. Inexpensive and simple approach pertaining to nanofibres approach is electrospinning method which capable to be scaled up and to produce 3 dimensional, porous structure with high surface area. Vast studies on the tissue engineering pertaining to silk and the silk regenerative properties have been associated with the impressive mechanical strength of the silk.